Reaching for both justice and peace in Colombia: Understanding the Special Jurisdiction for Peace’s mixed approach (using both retributive and restorative justice) to deal with international crimes - Sarkin, Jeremy (Contemporary justice review, 2023)
In the wake of the five-decade-long armed conflict in Colombia, the Comprehensive System of Truth, Justice, Reparation, and Non-Repetition was created as an ambitious system to deal with past crimes. It aims at engaging with all the pillars of transitional justice to ensure long-lasting peace and stability. Within this system, the Special Jurisdiction for Peace is tasked with delivering justice, while contributing to securing reconciliation and promoting peace. To do so, this transitional judicial body combines both retributive and restorative proceedings and sanctions. It embodies a mixed approach to criminal justice ensuring both justice and peace in the country. This approach, however, has been criticised as a lenient, and less than optimal, way of delivering peace and justice. Some see this as a methodology motivated by practical constraints and the lack of political will to pursue a more rigorous and prosecution-orientated model. This article aims at refuting such a perception by shedding light on the innovative mixed approach. It suggests that this approach might be well suited for delivering national and international criminal justice in transitional settings.